The Anticipated Proof in Arbitration - Ledesma Narváez, Marianella (2005)
The General Arbitration Law provides for the possibility of applying for pre-arbitration interim measures; however, it does not detail specific provisions regarding the securing of evidence by the jurisdiction prior to the commencement of arbitral proceedings. In this context, it is common that, prior to arbitral proceedings, situations arise in which it is necessary to resort to the jurisdiction to collect and protect evidence. In order to ensure the stability of the future process, it is possible to use procedural facilitators to ensure that the required evidence is available and protected when the arbitration is initiated. This is despite the existence of an arbitration agreement, as the use of evidence in advance in court is fully permissible. This situation does not affect the validity of the arbitration agreement and does not prevent the parties from later resorting to arbitration to resolve the dispute. Consequently, the objective of this measure is to guarantee access to judicial protection in exceptional circumstances and to preserve sources of evidence before arbitration is initiated.